2011
DOI: 10.1063/1.3643034
|View full text |Cite
|
Sign up to set email alerts
|

The quasi-free-standing nature of graphene on H-saturated SiC(0001)

Abstract: We report on an investigation of quasi-free-standing graphene on 6H-SiC(0001) which was prepared by intercalation of hydrogen under the buffer layer. Using infrared absorption spectroscopy we prove that the SiC(0001) surface is saturated with hydrogen. Raman spectra demonstrate the conversion of the buffer layer into graphene which exhibits a slight tensile strain and short range defects. The layers are hole doped (p = 5.0-6.5 x 10^12 cm^(-2)) with a carrier mobility of 3,100 cm^2/Vs at room temperature. Compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
301
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(339 citation statements)
references
References 27 publications
22
301
1
4
Order By: Relevance
“…Weakly interacting graphene layers such as graphene on C-face SiC exhibit a 2D peak located between those of monolayer and AB-stacked graphene. A G peak enhancement (comparable to 2D peak) is also observed 22 . Previous Raman studies on TG have attributed a narrowing and intensity increase of the 2D peak to interlayer coupling and a modified electronic band structure 16,21 .…”
Section: Resultsmentioning
confidence: 64%
“…Weakly interacting graphene layers such as graphene on C-face SiC exhibit a 2D peak located between those of monolayer and AB-stacked graphene. A G peak enhancement (comparable to 2D peak) is also observed 22 . Previous Raman studies on TG have attributed a narrowing and intensity increase of the 2D peak to interlayer coupling and a modified electronic band structure 16,21 .…”
Section: Resultsmentioning
confidence: 64%
“…Moreover, the charge carrier mobility of MLG is temperature * Corresponding author Tel: +49 371 531-32898. E-mail: Thomas.Seyller@physik.tu-chemnitz.de (Thomas Seyller) dependent [4] and it has been observed that this is a direct consequence of the presence of the buffer layer [10]. In recent years, various elements such as gold [11], lithium [12], silicon [13], fluorine [14], germanium [15], oxygen [16][17][18][19] and hydrogen [10,[20][21][22][23] have been intercalated between the buffer layer and SiC(0001) in order to modify the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen has been shown to work well, leading to so-called quasi-free-standing monolayer graphene (QFMLG) with improved electrical properties [10,[22][23]] when compared to normal MLG which resides on the buffer layer. Hydrogen is therefore a prime candidate for the future integration of quasi-free-standing graphene into devices.…”
Section: Introductionmentioning
confidence: 99%
“…H-QFMLG was obtained by annealing the buffer layer in molecular hydrogen [16,17], while O-QFMLG was prepared by annealing in water vapor [18]. Quasi-freestanding bilayer graphene (H-QFBLG) on Hterminated SiC(0001) was prepared by annealing MLG in hydrogen [16,19].…”
mentioning
confidence: 99%